1998
DOI: 10.4269/ajtmh.1998.58.144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recombinant dengue viral envelope B domain protein antigens for the detection of dengue complex-specific antibodies.

Abstract: To increase the specificity of dengue (DEN) diagnosis based on antibody detection, we have evaluated recombinant proteins as antigens that incorporate most of the B domain of the DEN virus envelope protein fused to the trpE protein of Escherichia coli (trpE-DEN). A pooled antigen consisting of trpE-DEN proteins representing all four serotypes of DEN virus was used in an indirect ELISA for the detection of IgG or IgM antibody. This assay was compared with a standard IgG indirect ELISA and an IgM-capture ELISA u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…The presence of many type-specific epitopes in DIII and its relatively stable conformation suggest that it might be useful as a virus-specific antigen. It has been shown by others that DIII can be independently expressed and retain much of its biological activity (3,10,21,22,24). The results presented here correlate closely with previously published information concerning the antigenic structure of the flavivirus E protein; however, some alternative explanations for these results could be considered.…”
supporting
confidence: 80%
“…The presence of many type-specific epitopes in DIII and its relatively stable conformation suggest that it might be useful as a virus-specific antigen. It has been shown by others that DIII can be independently expressed and retain much of its biological activity (3,10,21,22,24). The results presented here correlate closely with previously published information concerning the antigenic structure of the flavivirus E protein; however, some alternative explanations for these results could be considered.…”
supporting
confidence: 80%
“…Earlier investigations with other flaviviruses have also reported the presence of virusspecific epitopes within this region of the E protein (e.g., see references 6, 22, and 25), and other authors have suggested the utility of domain III from dengue virus types 1 to 4 or JEV as antigens for specific serological diagnosis of infections with those flaviviruses (10,24). These observations led us to investigate the utility of a recombinant, bacterially expressed domain III (r-EIII) antigen derived from the envelope protein of a North American WNV strain (385-99) for discrimination of WNV from other JE virus group infections.…”
mentioning
confidence: 99%
“…On glycoprotein E (10,14), a highly dengue virus typespecific antigenic side, the B domain or domain III, has been characterized (17). The short sequence of about 100 amino acids was expressed in Escherichia coli for the Japanese encephalitis (JE) virus by Mason et al (12) and for dengue viruses by Fonseca et al (4).…”
mentioning
confidence: 99%